HUBUNGAN PEMBERIAN SUSU FORMULA TERHADAP GEJALA ALERGI PADA BAYI KURANG DARI 6 BULAN DI KABUPATEN PIDIE - Rahmad Rahmad; Emiralda Emiralda (Jurnal Sains Riset, 2021)
Cow's milk allergy is one of the most common food allergies in children with an atopic history. If the child has atopic disease, it will be easily sensitized and develop into allergies to certain allergens, eg food, and cow's milk. In allergy sufferer gained a high level of IgE so that the mediator issued histamine and others that can cause allergic symptoms. The study aims to determine the relationship of infant formula feeding to allergic symptoms in children less than 6 months in Pidie. This type of research is an analytical observational with cross sectional design. The population in this research is all infants under 6 months old who are brought by their parents for consultation or immunizations to Posyandu. Sampling was conducted with a random sampling time of 3 months with a sample amount of 65 people. Data is then analyzed using the chi-square test. The results obtained that from a total of 36 respondents were given formula milk by 12 respondents (33.3%) Experienced allergies, and of a total of 29 respondents who were not given 3 respondent formula milk (10.3%) Experiencing allergies. Hypotheses test results using the Chi Square test obtained Ï-value = 0.029 which means there is a meaningful relationship of infant formula feeding to allergic symptoms in children less than 6 months in districts Pidie.Keywords: Allergy Symptoms, Infants Less Than 6 Months, Formula Milk